Control of molecular aggregation in symmetrically substituted pi-conjugated bulky poly(p-phenylenevinylene)s and their copolymers - Resmi, R.; Amrutha, S. R.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A new series of symmetrically substituted bulky PPV-copolymers based on poly(bis-2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEH-PPV) bearing tricyclodecane (TCD) pendants were synthesized to study the effect of chain aggregation in the pi-conjugated polymer backbone. The composition of the copolymers was varied up to 100 mol % and the structures of the copolymer were confirmed by NMR and FTIR. The molecular weights of the copolymers were obtained as M(w) = 11,500-1,78,800 depending on the TCD-incorporation in BEH-PPV. The origin of the pi-aggregation was investigated using mixture of solvents (polar or nonpolar) or temperature as external stimuli. Absorption, photoluminescence, and time-resolved fluorescence decay techniques were employed as tools to trace molecular aggregation in solution and solid state. The TCD-substituted bulky copolymers showed almost twice the enhancement in photoluminescence compared with that of BEH-PPV Solvent-induced aggregation studies of copolymers revealed the existence of strong molecular aggregation in BEH-PPV compared with that of bulky copolymers. Variable temperature studies further evidence for the reversibility of molecular aggregation on beating/cooling cycles and showed isosbetic points with respect to free and aggregated polymer chains. Time-resolved fluorescent studies confirmed the existence of free and aggregated pi-conjugated species with a life time of 0.1 to 1.0 ns. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2631-2646, 2009
Keywords: conjugated polymers; fluorescence; poly(p-phenylenevinylene); solution properties; Structure-property relationship

Supramolecular ring banded prototype liquid crystalline oligo(phenylenevinylene) - Amrutha, S. R.; Jayakannan, M. (Journal of Physical Chemistry B, 2009)
We report a new ring banded supramolecular structure in thermotropic liquid crystalline oligo(phenylenevinylene) (OPV) via a melt crystallization process. A series of structurally different OPV molecules were synthesized using tricyclodecanemethanol (TCD) as a bulky pendant unit to trace ring banded morphology. Among all, an OPV molecule with rigid bis-TCD units in the central core and flexible dodecyl chains at the outer phenyl rings (BTCD-BDD-OPV) was found to show ring banded morphologies, which is a first of its kind in T-conjugated materials. BTCD-BDD-OPV experiences strong aromatic pi-pi interactions in both film and liquid crystalline (LC) frozen stage. The pi-induced aggregation leads to lamellar self-assembly of OPV-mesogens that subsequently undergo helical crystal growth, thereby producing dark and bright ring banded patterns. Variable temperature X-ray diffraction analysis revealed the existence of three peaks at 27.07, 13.97, and 8.90 angstrom corresponding to 001, 002, and 003 fundamental layers, respectively, thus confirming the lamellar self-assembly of OPV-mesogens. Electron microscopic (SEM and TEM) analysis of the LC frozen sample showed images confirming helical microcrystalline assembly and providing direct evidence for the self-organization mechanism. Detailed photophysical experiments such as excitation, emission, and timeresolved fluorescence decay studies indicated that BTCD-BDD-OPV has very strong pi-pi interaction in both film and LC frozen stage, which was found to be main driving force for the formation of supra-ring structure. Upon illumination with light, the OPV chromophores in the LC phase were excited and the color of the samples turned into luminescent green ring bands.